(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تصطنع ألكيلات البنزن الخطيةLABs ذات سلاسل الألكيل C10-C14 ولتستخدم كمادة أولية في صناعة المواد الفعالة سطحياً من نوع سلفونات ألكيل البنزن الخطية (LASs ). تتشكل مركبات LASs لدى سلفنة LABs تحت تأثير H2SO4 أو SO3. عموماً ، يبقى قسماً من جزيئات LABs ، بمثابة جزيئات شائبة غير مسلفنة ، مع ناتج التفاعل LASs ، على الرغم من ارتفاع مردود عملية السلفنة. وبالتالي ستظهر مركبات LABs في المساحيق المنظفة المعتمدة على LASs . درس في هذا البحث مجموعة عينات من مساحيق المنظفات المحضرة ، جمعت من الأسواق المحلية بهدف تقدير نسبة ما تشكله مماكبات LABs فيها. تراوحت نسبة مماكبات LABs في المنظفات المدروسة بين13312.33- 2149.02μg/g. Linear Alkylbenzenes LABs with alkyl carbon numbers of 10 – 14 are manufactured as raw materials of Linear Alkylbenzenesulfonates LASs surfactants. LASs are synthesized by sulfonation of alkylbenzene with H2SO4 or SO3 .In spite of the fact that the yield of sulfonation is generally high, some of LABs remain unsulfonated and appear as contaminant in the detergents depending on LASs. In this research, we studied samples of detergents taken from the local market in order to estimate the percentage of LABs which existed in them . The concentration of LABs compounds detected in the samples of detergents were between 13312.33- 2149.02 μg/g .